Genome-Wide Identification and Expression Analysis of Cutinase Gene Family in Rhizoctonia cerealis and Functional Study of an Active Cutinase RcCUT1 in the Fungal–Wheat Interaction - Lu, Lin; Rong, Wei; Massart, Sebastien; Zhang, Zengyan (Frontiers in Microbiology, 2018)
Wheat (Triticum aestivum L.) is a staple food of more than 50% of global population. Rhizoctonia cerealis is the causal agent of sharp eyespot, a devastating disease of cereal crops including wheat. Cutinases produced by fungal pathogens play important roles in host-pathogen compatible interactions, but little is known about cutinases in R. cerealis. In this study, we identified a total of six cutinase encoding genes from R. cerealis genome, designated as RcCUT1-RcCUT6, analyzed their expression patterns during the infection, and determined virulence role for RcCUT1. All the proteins, RcCUT1-RcCUT6, contain a highly conserved GYSKG motif and another conserved C-x(3)-D-x(2)-C-x(2)-[GS]-[GSD]-x(4)-[AP]-H motif in the carbohydrate esterase 5 domain. The RcCUT1, RcCUT2, RcCUT4, and RcCUT5 are predicted to be secreted proteins containing four cysteine residues. These six cutinase genes had different expression patterns during the fungal infection process to wheat, among which RcCUT1 was highly expressed across all the infection time points but RcCUT6 was not expressed at all and the others were expressed only at certain time points. Further, RcCUT1 was heterologously expressed in Escherichia coli to obtain a purified protein. The purified RcCUT1 was shown to possess the cutinase activity and be able to induce necrosis, H2O2 accumulation, and expression of defense-related genes when infiltrated into wheat and Nicotiana benthamiana leaves. In contrast, RcCUT1 protein with serine mutation at the first motif had no cutinase activity, consequently lost the ability to induce necrosis. Noticeably, application of the purified RcCUT1 with R. cerealis led to significantly higher levels of the disease in wheat leaves than application of the fungus alone. These results strongly suggest that RcCUT1 serves as a virulence factor for the fungus. This is the first investigation of the cutinase genes in R. cerealis and the findings provide an important insight into pathogenesis mechanisms of R. cerealis on wheat.